Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1293/tox.23.253
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Pathogenesis of Foreign Body Granulomatous Inflammation in the Livers of Sprague-Dawley Rats

Abstract: Focal granulomatous inflammation developed in the livers of five 10-week-old male Sprague-Dawley rats. The characteristic features of this lesion were the presence of foreign body multinucleated giant cells engulfing calcium deposits and site-specific development in a fissure formed in a sub-lobation in the left lobe or interlobar fissure of the medial lobe of the liver. To clarify the pathogenesis of this lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other hand, he showed that granulomas are common spontaneous lesions in the liver. The liver changes may occur due to multiple causes such as drugs, bacterial, fungal, parasitic or viral infections, and liver or systemic disorders and are usually asymptomatic [36]. The liver examination after the injection of 1.7 mL/kg dose of iron oxide nanoparticles ( Figure 5(c)) indicates hepatocytes with moderate anisokaryosis, formation of chromocenters and nucleoli, and moderate granular cytoplasmic degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, he showed that granulomas are common spontaneous lesions in the liver. The liver changes may occur due to multiple causes such as drugs, bacterial, fungal, parasitic or viral infections, and liver or systemic disorders and are usually asymptomatic [36]. The liver examination after the injection of 1.7 mL/kg dose of iron oxide nanoparticles ( Figure 5(c)) indicates hepatocytes with moderate anisokaryosis, formation of chromocenters and nucleoli, and moderate granular cytoplasmic degeneration.…”
Section: Resultsmentioning
confidence: 99%